1988
DOI: 10.1111/j.1744-6570.1988.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Management Training and Education Practices in U.S. Companies

Abstract: A survey was systematically developed to assess issues related to management training and education, and it was sent to 1,OOO randomly selected U.S. companies with at least 1, OOO employees. Based on a 61% response rate, findings were obtained regarding issues such as needs assessment, management training and development approaches, reasons for selecting particular programs, characteristics of participants, how decisions are made regarding who wiII participate, preparation and follow-up of participants, evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
106
3
8

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 16 publications
17
106
3
8
Order By: Relevance
“…The dichotomy between "lower" and "higher" hierarchical position can also be found within high-level positions. Results from Saari et al (1988) showed that 66% of the businesses interviewed for their study offered university programs only to managers occupying top positions. In the context of nonmandatory training, results from Noe and Wilk (1993: 300) revealed that "across the three firms, position was the only variable that had a consistent significant relation with development activity."…”
Section: Hierarchical Positionmentioning
confidence: 99%
“…The dichotomy between "lower" and "higher" hierarchical position can also be found within high-level positions. Results from Saari et al (1988) showed that 66% of the businesses interviewed for their study offered university programs only to managers occupying top positions. In the context of nonmandatory training, results from Noe and Wilk (1993: 300) revealed that "across the three firms, position was the only variable that had a consistent significant relation with development activity."…”
Section: Hierarchical Positionmentioning
confidence: 99%
“…It should be noted that Reaction measures are the most common form of training evaluation (Brown, 1980;Saari, Johnson, McLaughlin, & Zimmerle, 1988;Swierczek & Carmichael, 1985).…”
Section: Reacionmentioning
confidence: 99%
“…Terpstra & Rozell, 1993 5. Training and development Saari et al, 1988 6. Implement highly developed internal labor markets Baron et al, 1986a;Ferris et al, 1992 7.…”
Section: Resultsmentioning
confidence: 99%